Prospective Cohort Study on Refractive Changes after Trabeculectomy - Kentaro Iwasaki; Yoshihiro Takamura; Shogo Arimura; Takahiro Tsuji; Takehiro Matsumura; Makoto Gozawa; Masaru Inatani (Journal of Ophthalmology)
We prospectively evaluated refractive changes in the eyes of 97 patients who underwent trabeculectomy at Fukui University Hospital, Fukui, Japan. The primary outcome measure was the refractive change after trabeculectomy. Secondary outcome measures included postoperative complications and prognostic factors for refractive change. We observed a progressive and significant mean refractive myopic shift of −0.80 D at 12 months after surgery. In phakic eyes, the mean myopic refractive shifts progressed significantly by −0.46 D at 3 months after surgery (P=0.003), by −0.52 D at 6 months (P=0.012), and by −1.31 D at 12 months (P<0.001). In the pseudophakic eyes, we found no significant refraction progression at any of the postsurgery follow-up visits. Our multivariable analyses showed that lens nuclear color grade change was a significant prognostic factor for refractive myopic progression (P<0.001). Trabeculectomy causes refractive myopic progression in phakic eyes. Nuclear sclerotic cataract progression is associated with refractive myopic shift after trabeculectomy. This trail is registered with UMIN000007813.